The hypotenuse is
times the length of each leg 'a'. Triangle XYZ is a isosceles right triangle, therefore the Pythagoras theorem becomes and this can be evaluated by using properties of isosceles triangle.
According to the statement
we have given that a theorem and we have to prove it.
So, For this purpose,
The given information is :
Isosceles triangle XYZ where
![Angle Z = 90^{0}](https://tex.z-dn.net/?f=Angle%20Z%20%3D%2090%5E%7B0%7D)
Let the sides of triangle XYZ be a, b, and c. Then side XY = c, YZ = b and ZX = a.
Now, it is given that triangle XYZ is isosceles triangle therefore, the shorter sides must be equal that is, a = b.
Now use Pythagoras theorem
![a^{2} + b^{2} = c^{2}](https://tex.z-dn.net/?f=a%5E%7B2%7D%20%2B%20b%5E%7B2%7D%20%3D%20c%5E%7B2%7D)
But here a= b then the equation become
![a^{2} + a^{2} = c^{2}](https://tex.z-dn.net/?f=a%5E%7B2%7D%20%2B%20a%5E%7B2%7D%20%3D%20c%5E%7B2%7D)
Then after solving it become
![2a^{2} = c^{2}](https://tex.z-dn.net/?f=2a%5E%7B2%7D%20%3D%20c%5E%7B2%7D)
And here we have to find the value of the hypotenuse,
so we solve it for c.
Then
![c = a\sqrt{2}](https://tex.z-dn.net/?f=c%20%3D%20a%5Csqrt%7B2%7D)
From this it is clear that the
it can be concluded that the hypotenuse is times the length of each leg 'a'.
Learn more about Pythagoras theorem here
brainly.com/question/343682
#SPJ1